A simple non-invasive method to collect soft tick saliva reveals differences in Ornithodoros moubata saliva composition between ticks infected and uninfected with Borrelia duttonii spirochetes - Filatov, Serhii; Dyčka, Filip; Sterba, Jan; Rego, Ryan O.M. (Frontiers in Cellular and Infection Microbiology, 2023)
We developed a new simple method to assess the composition of proteins in the Ornithodoros moubata saliva. To collect naturally expectorated saliva from the ticks, we employed an artificial membrane feeding technique using a simple, chemically defined diet and submitted the collected native saliva samples for liquid chromatography-mass spectrometry (LC-MS) analysis. These experiments were conducted with groups of uninfected ticks as well as with B. duttonii infected ticks. The ticks exhibited a fair feeding response to the tested diet, engorgement rates reaching between 60-100% of ticks per feeding chamber. LC-MS analysis identified a total of 17 and 15 proteins in saliva samples from the uninfected and infected ticks respectively. Importantly, the analysis was sensitive enough to detect up to 9 different proteins in the saliva containing diet upon which as few as 6 nymphal ticks fed. Some of the proteins identified are well known for their immunomodulatory activity in a vertebrate host, whereas others were structural or “housekeeping” proteins and their finding in the naturally expectorated saliva confirms that they can be secreted and having some roles at the tick-host interface. Most notably, some of the proteins that have long been suspected as important for vector-pathogen interactions of Borrelia spirochetes were detected only in the samples from infected ticks, suggesting that their expression was altered by the persistent colonization of the tick’s salivary glands by spirochetes. The simple method described herein is an important addition to the toolbox available to study the vector-host-pathogen interactions in the rapidly feeding soft ticks.